Nurse Caring: A Review of the Literature - Potter, Danita R.; Fogel, Joshua (International Journal of Advanced Nursing Studies, 2013)
The purpose of this paper was to review the literature on caring among nurses. The approach utilized studies on nurse caring behaviors in a variety of patient care settings. Articles published between 1987-2012 in the CINAHL, Medline, and PubMed databases were used. Overall, fourteen different articles were deemed relevant and were included in the review. The review articles were grouped into three categories which were Acute/Surgical, Community/Institutionalized, and Postpartum/Childbirth. In conclusion, human needs assistance was a consistent aspect of caring valued by patients.  We recommend that nurses learn their patient’s likes and dislikes while also providing for topics related to patient physical needs. Also when caring for children, nurses should use entertainment and humor as part of their caring approach.